When the Periphery Meets the Core of a Party-Press System: Remember Comrade Lei Feng in China’s Shifting Media Kaleidscope - Ji, Pan (International Journal of Humanities and Social Science Research, 2018)
At the epicenter of China’s reform, media adapt their propagandist role to different extents. They present distinct images about China’s Communist past. Against the backdrop, we examine media reconstructions of Lei Feng, a Communist icon CCP created in the 1960s. Drawing on media reform and collective memory literature, we find party-organ newspapers draw on altruism and loyalty in his original image to promote social stability and economic development for present purposes. Meanwhile, user generated contents in cyberspace question the authenticity of Lei Feng’s official records. Different reconstructions collide in online discussions. When commemoration is linked to chronicling, Lei Feng becomes a demoralizing lie; when not, a symbol for much-needed virtues in the present. Implications for understanding China’s media reform and for China’s collective memorization of revolutionary heroes are discussed.